Effects of organic and inorganic pollutants on the quality of river water and evaluation of possible negative effects on human health in the Eastern Cape Province - Vumazonke, Sesethu (Rhodes University, Faculty of Pharmacy, Pharmacy)
The quality of river water has been gradually decreasing for the past years due to pollution by faecal pathogens, organic and inorganic contaminants. This has caused environmental concern which led to the creation of a large area of research in many countries. In this study, the quality of river water was monitored by measuring physicochemical properties, bacteriological quality, screening of pharmaceuticals and biomonitoring water quality using aquatic macroinvertebrates. The physical parameters indicated the following; chemical oxygen demand ranged from 6 to 45 mg/L, turbidity ranged from 0.00 to 718 NTU, pH ranged from 5.89 to 9.77 and electric conductivity ranged from 0.00 to 2.95 mS. The concentrations of chemical parameters included phosphate ranged from 0.00 to 16 mg/L, chloride ranged from 80 to 518 mg/L, ammonium ranged from 5 to 279 mg/L, nitrate ranged from 0 to 50 mg/L, nitrite ranged from negative to positive, iron concentration was 0 mg/L in all the rivers throughout the sampling seasons while sulphate ranged from 5 to 103 mg/L. The bacteriological quality of river water ranged as follows; total coliform ranged from 0.20 to 255682 cfu/100 mL, faecal coliform ranged from 0.02 to 1091 cfu/100 mL and heterotrophic bacteria ranged from 213 to 1153543 cfu/mL. Several bacterial species were identified with analytical profile index kit with Klebsiella oxytoca, Vibrio alginolyticus, Providencia stuartii, Ewingella Americana, Providencia alcalifaciens/ rustigianii, Enterobacter cloacae, Leclercia adecarboxylata, Proteus penneri, Aeromonas salmonicida ssp salmonicida and Escherichia coli being the most dominant pathogenic bacteria present in the rivers. Pharmaceuticals screening was conducted using enzyme-linked immunoassay kits with fluoroquinolones detected in a concentration range of lower than detectable limits (LDL) to 0.4 ppb while sulfamethoxazole was in a concentration range of LDL to 1.4 ppb. Pre-concentration and extraction of the target pharmaceuticals in water samples were conducted by lyophilization followed by solid-phase extraction on Water Oasis HLB cartridge and ultra-performance liquid chromatography- electron spray ionization tandem mass spectrometry was used for detection of the compounds. The antibiotics detected were sulfamethoxazole at a concentration range of LDL to 3484 ng/0.5 L, clarithromycin at 2.4 to 1640.2 ng/0.5 L and erythromycin at LDL to 372.1 Î¼g/0.5 L and anti-epilepsy drug detected was carbamazepine at a concentration of 40.9 to 18288.1 ng/0.5 L in river water samples. Ibuprofen and ciprofloxacin were not detected. The biological quality of river water was assessed using aquatic macroinvertebrates. The presence of highly sensitive families such as Heptageniidae, Crambidae and Glossosomatidae was a confirmation that the quality of river water was in a good state on upper stream sites, while middle stream and lower stream sites were impacted.
Keywords: Water Pollution -- South Africa -- Eastern Cape; Water quality -- South Africa -- Eastern Cape; Physicochemical process; Drug resistance in microorganisms; Aquatic invertebrates